Financing global policies: but why? - Sylviane Guillaumont Jeanneney; Jean-Michel Severino (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Public financial flows to developing countries serve a multitude of purposes, the growing number of which has led over time to an incoherent institutional landscape of international financing. Institutional fragmentation has profound consequences for the effectiveness of policies. Starting from the achievements of official development assistance, our reflection seeks to clarify the aims of planetary collective action, by distinguishing three main objectives: ensuring the convergence of income between developing countries and industrialized countries; ensuring a foundation of global solidarity; fight against global public evils. This mapping allows us to present a first sketch of what could be an inventory of international financial flows according to a new nomenclature that would be collectively accepted by donors and recipients of flows. But since there are overlaps between the objectives, it is not possible to rigorously separate the objectives of growth, redistribution and the management of global public goods. We offer slightly more complex but still manageable procedures for tracking international flows. Accurate mapping of financial flows could avoid two main pitfalls of the current system, an excessively compassionate vision of the needs of low-income countries at the expense of the requirement to catch up on their economies, and in the face of the climate emergency, priority given to climate change mitigation projects at the expense of those specifically aimed at adaptation in low-income countries or more generally at their development.
Keywords: 330